Analysis of "Burekol" Procedures and Benefits for Generation Z at Bank Syariah Indonesia (BSI): Analisis Prosedur dan Manfaat “Burekol" di Bank Syariah Indonesia (BSI) Bagi Generasi Z - Firdaus, Rahmat; Rahmah, Hudiya (Jurnal Hukum Ekonomi Syariah : AICONOMIA, 2024)
The purpose of this study is to determine and analyze the procedures and benefits of opening an online account (BUREKOL) Bank Syariah Indonesia (BSI) for Generation Z (Study of Students of Sharia Banking Study Program UIN Mahmud Yunus Batusangkar). This type of research is field research or field research, using a qualitative descriptive approach. The results of this study found that the procedure (BUREKOL) (BSI) is to download the BSI Mobile application, then select Open an Account, then select the Card Type, then the customer prepares the required documents for opening a BSI account, then fills in complete and correct personal data, uploads a photo of the ID card, a photo of the customer holding the ID card, and the NPWP card, the customer verifies via video call service with the BSI officer, and finally waits until the account opening is approved. The benefits of (BUREKOL) are that it does not take a long time to open an account, can be accessed anywhere, does not require a long time to process, free administration fees, account opening services can be done by yourself via cellular telephone for 24 hours a day, do not bother filling out forms at the bank, have mobile banking and internet banking facilities, and are easy to process.